Assessment of Normal Liver Size among Adults by Ultrasonography in Kathmandu Medical College - Shrestha, Elina; Thapa, Narayan Bikram; Tayal, Ashok (Nepalese Journal of Radiology, 2021)
Introduction: Ultrasonography is cheap, non-invasive, reliable, fast method of diagnostic investigation in the measurement of liver size. Normal range of liver size helps to diagnose hepatomegaly sonologically which may be clinically inapparent. Thus warrants further clinical evaluation and other investigations for the prevention of major hepatic comorbidities. Methods: A prospective, cross-sectional study was conducted on 400 adults with sonographic findings unrelated to liver pathologies. The liver was measured in right midclavicular line from hepatic dome to lower hepatic margin. The correlation between liver size and age, sex, weight, height, body mass index (BMI), and body surface area(BSA) was calculated. The data were properly analyzed in SPSS version 20 software. Results: Out of 400 patients, a male: female ratio of 1:1.25, and the age group was ranging from 20 years to 83 years with a mean age of 48.10±14.86 years were included. The mean liver length in males was 15.05 ± 0.27 cms, females were 14.32 ± 0.29 cms and the total population was 14.73 ±0.46 cms. There was a strong statistically significant correlation between liver size and height, weight whereas the correlation between liver span and BSA was moderate to weak but significant. Similarly, there was a weak but significant correlation between liver size and BMI with no significant association between liver size and age. Conclusion: Accurate assessment of liver size is of utmost importance in the evaluation of suspected hepatic pathologies.